Wieczorowy Kurs Księgowości Przebitkowej. (Gdynia : [s.n.], 1947)
Afisz inf. o kursach w Gimnazjum i Liceum Handlowymw Gdyni.
Keywords: Szkoły -- Polska -- Gdynia -- 1945-1970.; Gdynia (Polska) -- 1945-1970 -- druki ulotne